PERCEPTION OF 11% VAT RATE IN THE E-COMMERCE MARKET - Deri Yanto; Murdhaningsih; Giantoro Pamungkas (IJOSMAS, 2023)
Research related to the perception of the 11% VAT rate from digital market interaction activities through E-Commerce towards tariffs shows the relative level of application and understanding of the VAT rate from 10% to 11% with a high understanding of quantitative data through the electronic market. This states that the public is very enthusiastic about the tax rate in accordance with the application of the destination country. By going through a comparative analysis of the implementation of increased tax rates abroad. From the level of understanding, the community explains that there is a normal limit on the device in reporting data in the form of tax reporting.